Diversified Variants of Astrovirus MLB2 in Patients Following Hematopoietic Stem Cell Transplantation and the Evolutionary Rates and Patterns of the Virus. (July 2019) - Guo, Ke; Li, Li-Li; Zhang, Qing; Yu, Jie-Mei; Ye, Yan
We assessed the quasispecies heterogeneity of a human astrovirus MLB2 (HAstV-MLB2-YJMGK) in immunocompromised patients following hematopoietic stem cell transplantation and performed genetic and evolutionary analyses of HAstV isolates circulating worldwide. The result showed that the virus had diversified variants and a strong positive selection in the patient, indicating that such patients may be a reservoir for astrovirus. The time to the most recent common ancestor of MLB2 and classic HAstVs was around 1800 years, and it has a decline in effective population size of HAstVs in the late 100 years.